Prenatal Diagnosis of Neural Tube Defects: Evaluation of 112 Cases - Mahmut Tuncay Özgün; Cem Batukan; Dilek Kaya; Çağdaş Türkyılmaz; Mustafa Başbuğ (Medical Network, 2009)
OBJECTIVE: The aim of this study was to represent our experience of the prenatal sonographic diagnosis of NTDs at our institution during a five year period. STUDY DESIGN: All fetuses with a prenatally detected neural tube defect were included in this retrospective analysis. Demographic characteristics and prenatal ultrasound findings were presented. RESULTS: NTD was diagnosed in 112 fetuses, which represents 1.99% of 5605 fetuses scanned between 2004 and 2009. Mean maternal age and gestational week at the time of diagnosis were 25.5 ± 5.6 (17-40) years and 20.6 ± 6.3 (12-38) weeks, respectively. A total 78 pregnancies were terminated due to presence of anencephaly (n=21), encephalocele (n=14), open spina bifida (n=35) and iniencephaly (n=8). Selective fetocide was performed in a dichorionic twin pregnancy discordant for anencephaly. Five fetuses died in-utero. Twenty-one viable fetuses were delivered by cesarean section and 7 fetuses were delivered vaginally. Fifteen fetuses were operated during the neonatal period and of these, 4 (26.7%) died postoperatively. Of the operated fetuses, only two (13.3%) survived (both of which showing normal cranial findings during antenatal follow-up) without neurological or orthopedic sequels. CONCLUSION: NTDs carry mostly a dismal prognosis. Prenatal diagnosis of NTDs before viability is important for management.